2022
DOI: 10.3390/ijerph19020628
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Needs from a Household Perspective: An Empirical Study in Rural Empty Nest Families in Sinan and Dangyang, China

Abstract: This study aimed to explore the health service needs of empty nest families from a household perspective. A multistage random sampling strategy was conducted to select 1606 individuals in 803 empty nest households in this study. A questionnaire was used to ask each individual about their health service needs in each household. The consistency rate was calculated based on their consistent answers to the questionnaire. We used a collective household model to analyze individuals’ public health service needs on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…12 With the increasing social mobility of younger people in search for better job opportunities, the number of 'empty-nest' families in China where households are without adult children or whose adult children have left their parents' home, is expected to increase to 90% by 2030 according to China's National Committee on Ageing. 13 Family fragmentation with migration and emigration of adult children has resulted in a significant drop in family caregivers for older people in the same household. 12 Adult children often fulfil their filial piety by sending financial support to maintain their parents' living conditions, but little is known about whether these filial expressions ameliorate their parents' loneliness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 With the increasing social mobility of younger people in search for better job opportunities, the number of 'empty-nest' families in China where households are without adult children or whose adult children have left their parents' home, is expected to increase to 90% by 2030 according to China's National Committee on Ageing. 13 Family fragmentation with migration and emigration of adult children has resulted in a significant drop in family caregivers for older people in the same household. 12 Adult children often fulfil their filial piety by sending financial support to maintain their parents' living conditions, but little is known about whether these filial expressions ameliorate their parents' loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, demographic trends resulting from longer life expectancy and shrinking family size has raised the importance of intergenerational reciprocity 12 . With the increasing social mobility of younger people in search for better job opportunities, the number of ‘empty‐nest’ families in China where households are without adult children or whose adult children have left their parents' home, is expected to increase to 90% by 2030 according to China's National Committee on Ageing 13 . Family fragmentation with migration and emigration of adult children has resulted in a significant drop in family caregivers for older people in the same household 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative or sequential comorbidities, such as diabetes mellitus [12], cardiovascular diseases [13], malnutrition [14], dyslipidemia [15], etc., menopausal or perimenopausal syndrome due to persistent estrogen (E2) depletion in the body [16], loss of jobs [17], lack of sexual intimacy [18], and so forth are related indicators to that of the ENS and its severity. Studies have found that fathers too are affected by the departure [19]. This is one side of the issue.…”
Section: Introductionmentioning
confidence: 99%